Temporal and spatial strategies in an active place avoidance task on Carousel: a study of effects of stability of arena rotation speed in rats - Bahník, Štěpán (PeerJ, 2015)
The active place avoidance task is a dry-arena task used to assess spatial navigation and memory in rodents. In this task, a subject is put on a rotating circular arena and avoids an invisible sector that is stable in relation to the room. Rotation of the arena means that the subject’s avoidance must be active, otherwise the subject will be moved in the to-be-avoided sector by the rotation of the arena and a slight electric shock will be administered. The present experiment explored the effect of variable arena rotation speed on the ability to avoid the to-be-avoided sector. Subjects in a group with variable arena rotation speed learned to avoid the sector with the same speed and attained the same avoidance ability as rats in a group with a stable arena rotation speed. Only a slight difference in preferred position within the room was found between the two groups. No difference was found between the two groups in the dark phase, where subjects could not use orientation cues in the room. Only one rat was able to learn the avoidance of the to-be-avoided sector in this phase. The results of the experiment suggest that idiothetic orientation and interval timing are not crucial for learning avoidance of the to-be-avoided sector. However, idiothetic orientation might be sufficient for avoiding the sector in the dark.